К вопросу изученности болезней и паразитов выдры острова Сахалина - Беньковский, Л.М.; Головина, Т.И.; Щербина, Р.Д. (Вестник зоологии, 1973)
The data on diseases and parasites of otter from Sakhalin island are given by sources of literature and the author's own data. The pathology of the sick animals and the connections with other representatives of the fauna favouring otter infestation in the land are described.